Elevated pCO2 Level Affects the Extracellular Polymer Metabolism of Phaeodactylum tricornutum - Zhang, Wei; Tang, Xuexi; Yang, Yingying; Zhang, Xin; Zhang, Xinxin (Frontiers in Microbiology, 2020)
Extracellular polymeric substances (EPS) play an important role in diatom physiology and carbon biogeochemical cycling in marine ecosystems. Both the composition and yield of EPS in diatom cells can vary with environmental changes. However, data regarding how EPS production responds to environmental factors in diatoms is limited. Further, how such changes would affect their critical ecological roles in marine systems is also unclear. Here, we evaluated the physiological characteristics, EPS yields, EPS compositions, and gene expression levels of P. tricornutum under elevated pCO2 levels. Genes and pathways related to EPS metabolism in P. tricornutum were identified. Carbohydrate yields in different EPS fractions increased with elevated pCO2 exposure. Although the proportions of monosaccharide sugars among total sugars did not change, higher abundances of uronic acid were observed under high pCO2 conditions, suggesting the alterations of EPS composition. Elevated pCO2 increased PSII light energy conversion efficiency and carbon sequestration efficiency. The up-regulation of most genes involved in carbon fixation pathways led to increased growth and EPS release. RNA-Seq analysis revealed a number of genes and divergent alleles related to EPS production that were up-regulated by elevated pCO2 levels. Nucleotide sugar activation and accelerated glycosylation could be responsible for more EPS responding to environmental signals. Further, nucleotide sugar transporters exhibited increased expression levels, suggesting roles in EPS over-production. Overall, these results provide critical data for understanding the mechanisms of EPS production in diatoms and evaluating the metabolic plasticity of these organisms in response to environmental changes.